From Culture Shock to Academic Life: Narratives of an Indonesian Exchange EFL Student at a Midwest University in the United States - Musaldin, La Ode; Halim, Abdul; Zur, Sarjaniah; Atikah, Dewi; Syukri, Suhartini; Nurfaidah, Sitti (IAIN KENDARI, 2024)
This study aims to explore and narrate the culture shock experienced by the first author, an Indonesian EFL exchange student, during an academic exchange program at a Midwestern university in the United States. Using an autoethnographic approach, data were collected from the author's personal reflections, journals, and social media archives, then analyzed through a narrative method to present the lived experiences in a clear, chronological structure. The findings reveal that the first author experienced a range of emotions throughout all four stages of culture shock: honeymoon, frustration, adjustment, and adaptation. Each stage had a notable impact on his academic performance, emotional well-being, and motivation to engage with the host university’s academic and social environments. The study highlights the importance of cultural readiness and emotional resilience for exchange students. It also recommends that higher education institutions strengthen orientation programs and offer more holistic, culturally responsive support systems to help students navigate cross-cultural transitions effectively.